2008
DOI: 10.2500/ajr.2008.22.3241
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Antibiotic Care after Functional Endoscopic Sinus Surgery

Abstract: This study showed that postoperative care with amoxicillin/clavulante did not improve the short-term outcome of FESS on chronic rhinosinusitis or decrease bacterial growth 3weeks after FESS, although the long-term influence was not evaluated in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 8 publications
0
63
0
Order By: Relevance
“…As shown in Table 1, the mean ± SD age of this overall study population was 48.43 ± 13.34 years old; 57.49% were male (n = 215); 89.43% were white (n = 330); and 7.86% were black (n = 29). The clinically significant change of SNOT-22 score was defined as difference of at least 0.5 SD of the baseline SNOT-22 score in patients without asthma and NP 16,17 ; ie, 10.6. The prevalence of allergic rhinitis and Samter's triad were significantly higher in CRS patients with asthma and NP compared to patients without asthma and NP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1, the mean ± SD age of this overall study population was 48.43 ± 13.34 years old; 57.49% were male (n = 215); 89.43% were white (n = 330); and 7.86% were black (n = 29). The clinically significant change of SNOT-22 score was defined as difference of at least 0.5 SD of the baseline SNOT-22 score in patients without asthma and NP 16,17 ; ie, 10.6. The prevalence of allergic rhinitis and Samter's triad were significantly higher in CRS patients with asthma and NP compared to patients without asthma and NP.…”
Section: Resultsmentioning
confidence: 99%
“…Higher scores represent worse QOL. Clinically significant change of SNOT-22 score was defined as a difference of at least 0.5 standard deviations (SDs) of the baseline SNOT-22 score in the reference group, 15,16 which is the group of patients without asthma and NP in our study.…”
Section: Collection Of Qolmentioning
confidence: 99%
“…However, the treatment course was limited to just 2 days of cefuroxime. In another study, amoxicillin/clavulanate was compared to a control group for 3 weeks following ESS [ 16 ]. No differences in rates of positive bacterial culture, symptom scores, or endoscopic scores were noted.…”
Section: Specific Therapy Postoperative Antibioticsmentioning
confidence: 92%
“…In 2008, Jiang et al [16] demonstrated no short-term benefit in either symptom or endoscopic scores to postoperative amoxicillin/ clavulanate therapy at 3 weeks. Three years later, Liang et al [17] showed that there was no difference amongst patients treated with Chinese herbal medicine, amoxicillin, or placebo in the postoperative period in the Chinese version of the Rhinosinusitis Outcome Measure (CRSOM-31) and endoscopic scores.…”
Section: Evidence Regarding Postoperative Antibioticsmentioning
confidence: 99%